Integration of movements in methodical activities of students of a pre-school teacher college - Lazić Svetlana; Matović Mirjana; Velišek-Braško Otilia (University Educons, Faculty of Sports and Tourism, Novi Sad, 2019)
The topic of the research is connecting multiple areas of pedagogical and educational work during realisation of activities in five fields of students' practical work with pre-school children. The goal of the research is assessment of the extent to which the students plan the integration of movements, application of movement activities and activation of the locomotor system during preparation for the realisation of the five methodical areas. 144 students' preparations were analysed, all from applied, professional, obligatory courses that students of pre-school teacher colleges attend in their second and third years of bachelor studies. It has been established that there was an integration of content, but not of action, as well. In anticipating one's own work as a prerequisite for stimulation and development of movement activities in children, students do not integrate the content and practice to a sufficient degree.